Physiological and technical characteristics of elite young basketball players - Apostolidis, N.; Nassis, G. P.; Bolatoglou, T.; Geladas, N. D. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: The aim of this study was 2-fold: a) to describe the physiological and technical characteristics of elite young basketball players, and b) to examine the relationship between certain field and laboratory tests among these players. METHODS: Thirteen male players of the junior's Basketball National team (age: 18.5 +/- 0.5 years, mass: 95.5 +/- 8.8 kg, height: 199.5 +/- 6.2 cm, body fat: 11.4 +/- 1.9%, means+/-SD) performed a run to exhaustion on the treadmill, the Wingate test and 2 types of vertical jump. On a separate day, the field tests (control dribble, defensive movement, speed dribble, speed running, shuttle run and dribble shuttle run) were conducted. RESULTS: Maximal oxygen uptake (VO2max) and ventilatory threshold were 51.7 +/- 4.8 ml/kg/min and 77.6 +/- 7.0% VO2max, respectively. Maximum power output was 10.7 +/- 1.3 Watts/kg and mean power (Pmean) 8.0 +/- 0.7 Watts/kg. Counter-movement and squat jump height were 40.1 +/- 3.7 and 39.8 +/- 4.0 cm, respectively. Performance in control dribble (13.70 +/- 0.96 s), speed dribble (4.24 +/- 0.75 s), high intensity shuttle run (27.90 +/- 1.04 s) and dribble shuttle run (29.50 +/- 1.22 s) was correlated with Pmean (r=-0.58, r=-0.62, r=-0.56 and r=-0.73, respectively, p<0.05). Percent body fat was negatively correlated with all the above field tests (r=0.63, r=0.57, r=0.66, r=0.65, respectively, p<0.05). CONCLUSION: These players presented a moderate VO2max and anaerobic power. The significant correlation between Pmean and certain field tests indicates that these tests could be used for the assessment of anaerobic capacity of young basketball players.